The Female Employees’ Readiness On Flexible Working Arrangements In Malaysia - Mohd Isa, Salmi; Musa, Mazidah; Chong , Ang Gee (2016)
Flexible working arrangements (FWA) has become an important aspect in Human Resource Management policy for organization to attract and retain talented employees in the organization. The low female participation in labour workforce has motivated this study to be conducted. It aimed to provide insight to the employers on female employees special needs and their readiness to embrace flexible working arrangements if the resources were made available to them. “Readiness” to embrace flexible working arrangement was not previously studied in the flexible working arrangements field, hence a considerable amount of attention has been paid to construct the theoretical framework. An instrument is developed based on a critical review of Person-Environment (PE) fit theory that is able to explain the readiness of female employees depending on the situation surroundings them. Thus, this study postulates into three microsystems that are family (family responsibility, perceived benefits), work (career advancement, company policy), and community (supportive workplace) in PE fit theory that creates demands and resources (readiness on flexible working arrangements). The integrated approach has explained how the independent variables family responsibility, perceived benefits, career advancement, company policy impact on the readiness on flexible working arrangements and the mediating role of supportive workplace. The results shown that hypothesised relationships were partially supported, i.e family responsibility and perceived benefits was positively related to readiness to embrace flexible working arrangements. Besides, supportive workplace mediated the relationship between perceived benefits and company policy in relation to readiness to embrace flexible working arrangements. These findings have also demonstrated that women with different experience have different demands in flexible working arrangements. Findings have shown that 60 percent of the respondents were ready to embrace flexible working arrangements except for part time work options. Besides, this study has found that respondents with no children favored in compressed work schedule as the statistical result recorded at p<0.05. The output of this study would be able to benefit policy makers, organizations and practitioners to establish flexible working arrangements in Malaysia. Consequently, corporate companies would be able to attract more female employees in the business, resulting in higher productivity.